AN ANALYSIS OF STUDENTS’ ABILITY AND DIFFICULTIES IN WRITING DESCRIPTIVE TEXTS - Juanita Siahaan (Journal of English and Education, 2013)
This paper repotrs on an investigation towardsthe tenth graders’ ability and difficulties in writing descriptive text in one class of one senior high school in Bandung. The research used a qualitative case study as the method and texts analysis as the data collection techniques. Nine texts written by Low, Mid, and High achievers were analyzed in terms of schematic structure and linguistic features using Systemic Functional Linguistics. The findings revealed that the students representing the middle and high achievers had a good control about the schematic structure of descriptive text. They also were able to use appropriate linguistic features. On the other hand, it was also revealed that the low achievers were still confused in identifying the schematic structure of descriptive text. Moreover, the low achievers still needed a lot of improvement as they still made a lot of mistakes in the text they wrote.  Keywords: Descriptive Text, Systemic Functional Linguistics